Global versus local brand: perceived quality and status-seeking motivation in the automobile industry - Ho, Jessica Sze Yin *; Ong, Derek Lai Teik *; Wang, Pheik Ing *; Tay, Grace Tsu Phing *; New, Chye Peng * (2012)
The purpose of this research is to examine the influence of status-seeking motivation on perceived quality of a global versus local automobile brand in Malaysia. The data for this research was collected through 303 questionnaires from young working adults within the Klang Valley. Data was analysed using repeated measure t-test and results show that a global brand is generally preferred in terms of perceived quality in regards to wealth, achievement and enhance social standings. Likewise, regardless of high or low status-seeking motivation, a global brand is still preferred over a local brand.